Raven : a trickster tale from the Pacific Northwest - McDermott, Gerald (New York : Scholastic, 1993)
Raven, a Pacific Coast Indian trickster, sets out to find the sun.
Keywords: Indians of North America -- Northwest, Pacific -- Folklore